Residencia Sierra Vertientes : Abraham Zabludovsky, arquitecto, 1960 (2001)
Información gráfica sobre la casa mencionada.
Keywords: VIVIENDAS UNIFAMILIARES; VIVIENDAS URBANAS; MEXICO; DISTRITO FEDERAL; ZABLUDOVSKY, ABRAHAM